A Comparative Study of Silphium spp. Antioxidant Activity - Vergun, Olena; Shymanska, Oksana; Rakhmetov, Dzhamal; Fishchenko, Valentyna; Ivanišová, Eva (Agrobiodiversity for Improving Nutrition, Health and Life Quality, 2023)
This study aimed to evaluate the parameters of antioxidant activity of different parts of Silphium spp. during budding and flowering periods. The four species of Silphium L. genus from the experimental collection of the Cultural Flora Department of M.M. Gryshko National Botanical Garden of the NAS of Ukraine were prepared and used in this research. Total polyphenol content was from 12.32 (S. asperrimum, stems at the budding) to 95.21 (S. laciniatum, leaves at the flowering stage) mg GAE.g-1 DW depending on the organ and stage of vegetation. The total content of phenolic acids in ethanol extracts of investigated plants was from 3.52 (S. asperrimum, buds at the budding) to 34.58 (S. laciniatum, leaves at the flowering) mg CAE.g-1 DW. The total flavonoid content in investigated extracts was from 3.67 (S. perfoliatum, stems at the budding) to 57.31 (S. laciniatum, leaves at the budding) mg QE.g-1 DW. Antioxidant activity was determined by two assays namely the DPPH method and molybdenum-reducing power of extracts and was from 3.33 (S. trifoliatum, stems at the budding) to 9.11 (S. laciniatum, flowers at flowering) mg TE.g-1 and from 29.11 (S. trifoliatum, stems at the budding) to 185.22 (S. laciniatum, leaves at the flowering) mg TE.g-1 DW, respectively. It was found a very strong correlation between total polyphenol compounds, flavonoids, phenolic acids, and molybdenum reducing power r = 0.715–0.905. A weak or moderate correlation was found between DPPH scavenging activity and investigated phenolic compounds (r = 0.110–0.522). Obtained data can be useful for further deep biochemical investigation of plant raw of Silphium spp. and in livestock nutrition branch.